(3ZQQ GdeYGfis - (3CMeO Hf eMeO Hf Ydj Hf GdMSjf Hf Ojfhjg , CHh GdYHGS , J b (B6 (3g`s ((3Ydi Hf GdMSf Hf eMeO Hf YHO Gddg s)
(3ChdgG (B:s
(3GdMeO ddg Ydi GdBjI GdYXGe hSfg GdLSGe hGdUdGI Ydi eMeO NjQ GdCfGe s
(3BNQgG (B:s
(3jJdhg ai GdQGHYI ShQI Gdcga YR hLd cJHg GdabjQ Edi QMeI Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
(3eUOQ GbJfGA GdCUd (B:s
(3SHgSdGQ GjQGf (B(207) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs